A selective triarylmethine-based spectroscopic probe for Zn2+ ion monitoring. (December 2019) - Lee, Naru; Ly, Nguyen Hoang; Kim, Jong Seung; Jung, Hyo Sung; Joo, Sang-Woo
Abstract: We report the synthesis and application of a novel probe of the di-2-picolylamine (DPA)-conjugated triarylmethine (TAM) dye which has aimed at detecting Zn 2+ ions. The 1:2 binding stoichiometry is estimated between Zn 2+ and DPA-TAM according to Job's plot diagram and density functional theory (DFT) calculations. The increment of Zn 2+ ion concentrations leads to the elevated SERS intensity of DPA-TAM on gold nanoparticles (AuNPs) due to the intermolecular chelation between the Zn 2+ ion and DPA-TAM. Our synthetic spectroscopic probe shows [Zn 2+ ]-correlated SERS intensities with an estimated detection limit of 50 μM. This is due to a plasmonic enhancement effect from the well-dispersed metal nanoparticles to DPA-TAM-AuNP aggregates, which is activated by Zn 2+ ion. The prepared DPA-TAM-AuNP system can also be successfully applied to monitoring of intracellular Zn 2+ ions both in human cervical carcinoma HeLa cells in vitro and daphnia in vivo through dark-field microscopy (DFM)-equipped Raman cellular imaging. Our DPA-TAM-AuNP system provides a new insight in potential applications of bioanalytical Zn 2+ ion detection methodology. Graphical abstract: Image 1 Highlights: Di-2-picolylamine (DPA)-triarylmethine (TAM) was synthesized for Zn 2+ ion detection. The 1:2 binding stoichiometry was estimated between Zn 2+ and DPA-TAM. Zn 2+ led the interparticle aggregation of gold nanoparticles (AuNPs) via DPA-TAM. Zn 2+ with a detection limit of ∼50 μM increased SERS intensities of DPA-TAM on AuNPs. DPA-TAM-Zn 2+ system was applied to HeLa cells in vitro and daphnia in vivo.